CRAMER’S RULE IN INTERVAL MIN-PLUS ALGEBRA - Siswanto Siswanto; Ade Safira Septiany (Barekeng)
A min-plus algebra is a set ,  where  is the set of all real numbers, equipped with the minimum  and addition  operations. The system of linear equations  in min-plus algebra can be solved using Cramer's rule. Interval min-plus algebra is an extension of min-plus algebra, with the elements in it being closed intervals. The set is denoted by  equipped with two binary operations, namely minimum  and addition . The matrix with notation  is a matrix over interval min-plus algebra with size . Since the structure of min-plus algebra and interval min-plus algebra are analogous, the system of linear equations  in interval min-plus algebra can be solved using Cramer's rule. Based on the research results, the sufficient conditions of Cramer's rule in interval min-plus algebra are  for , and . The Cramer rule is .